Online parenting whatsapp group virtual ethnographic study child friendly community - Diki Wibowo; Pupu Wasngadiredja (Institute of Accounting Research and Novation (IARN), 2023)
This research was conducted through the Child-Friendly family WhatsApp group, a community formed for teachers and parents at Zaidan Educare and now has more than 200 members with diverse backgrounds. The purpose of this study was to find out the context of messages conveyed in online seminars in WhatsApp groups for Child-Friendly families, find out the rules of interaction agreed upon by all members, and find out the reality that occurs in online seminar rooms and their relation to offline spaces. The research method used is qualitative with a virtual ethnographic approach. The results of the research show that the main idea in this online seminar is about parenting. There are rules to follow, such as members are not allowed to share writing from other sources and only material compiled directly by caregivers and group permanent resource persons can be published. The link between offline and online spaces forms a reciprocal pattern of knowledge and practical techniques in parenting.